Cooperação internacional e transferência de políticas públicas no campo da comunicação social: o papel da UNESCO na reforma da radiodifusão do Brasil - Mello, Simone Cardozo de Assumpção (2013)
This dissertation was developed within a Master’s program on Management at the Grande Rio University (UNIGRANRIO), and its main general purpose is, to assess if and how the policy recommendations made by UNESCO in 2011, influenced the national debate on the reform of the Brazilian social communication system. In order to reach this objective, the dissertation reviewed two main concepts in the academic literature: international cooperation and policy transfer. Moreover, it presents the results of semistructured interviews undertaken with key informers who are actively-working in the field. The text that follows is structured into three chapters: in the first chapter, we analyzes the links between social communication and international cooperation for development through the following issues: the field of the communication mass media, the role of the international cooperation in this area, the present context of the Brazilian social communication sector and the debate about reform in Brazilian broadcasting. In the second chapter, we introduce our theoretical references – international cooperation and policy transfer - and the analytical framework used for the empirical study. The third chapter presents the case study on UNESCO’s influence on Brazilian public policies of social communication based on the following sources: the three official studies published by the Organization, a presentation of the broadcasting context in ten countries, and the systematization of the results of the interviews that we have undertaken. The conclusion shows a set of elements which were considered relevant to answer our primary research question, and points out new issues for the research agenda. Therefore, although the role of the Brazilian social communication is complex and contradictory, there is no doubt that its role must be reformed and improved.